A Sustainable Social Development Model Based On Cultural Barriers - Amini , Abbas; Jafarinia, Gholamreza; Ghalehteimouri, Kamran Jafarpour; Gorgin, Bagher (Indonesian Journal of Social Research (IJSR), 2024)
Numerous studies have been conducted on effective, sustainable development, but they may not benefit local communities. Recognizing the potential for spatial development within a city and its various sectors, it is evident that specific barriers, particularly cultural ones, must be addressed. This study seeks to create a socially stable development model for Beshagard City by tackling the cultural challenges present in the community. The research utilizes a mixed methodology incorporating both qualitative and quantitative approaches. The study population consists of students living in urban and rural areas of the city. Following Morgan's Table for sample size determination, a maximum of 384 participants were chosen for the quantitative segment of the study. Additionally, qualitative data was gathered through interviews with 20 individuals, including professors, urban development sustainability experts (10 individuals), and representatives from cultural heritage organizations (10 individuals). Data was analyzed using SPSS and Lisrel software in a Windows environment, encompassing descriptive and inferential statistical analyses. Descriptive statistics were utilized to examine data levels and rankings among the student population. Moreover, a structural equation model was utilized to devise an appropriate development model for achieving social stability. Data was analyzed using Microsoft Excel, SPSS, and Lisrel software. The research findings reveal that cultural factors significantly impact the underdevelopment of Beshagard City, as evidenced by the t-test results, with a calculated t-value (8.09) exceeding the standardized t-value of 1.96 at a 95% significance level. The importance of culture in sustainable development and the promotion of social justice cannot be emphasized enough. The research clearly shows that culture is a key factor in the progress of any community. Ignoring or underestimating this essential element can lead to the downfall of all development efforts.